Makna Sholat Wustho dalam Al-Qur’an: Kajian terhadap Penafsiran al-Maraghi dan Jalalain - Syamsiyah, Siti Iis (Al-Fath, 2020)
Al-Qur’an is a holy book that has never been devoid of discussion until now. This is because most of the verses open up opportunities for various interpretations of meaning. One area of study that is still being debated is the verse regarding wustha prayer. Some call it witir prayer, some call it dzuhur prayer, and some call it Asr prayer. This difference can certainly be a factor of sharper differences among the ummah if they do not understand the arguments of each of these opinions. For this reason, it is deemed important to raise this issue as a topic of study, by raising the opinions of two exegete figures as a comparison of interpretation. Based on the background above, the problem formulations in this thesis are: 1). How do al- Maraghi and Jalalain view the meaning of wustha prayer? 2). How do different views on the meaning of wustha prayer occur between the interpreters?